Road Trips and Guideposts: Identifying and Navigating Ethical Tensions in Research-Based Theater. (February 2023) - Nichols, Jennica; Cox, Susan M; Guillemin, Marilys
Research-based Theater (RbT) combines research and theater to create novel opportunities for inquiry and knowledge translation. Ethical tensions are part of this process. We explore some tensions that can emerge through three types of ethics: professional ethics, institutional research ethics, and everyday ethics. We then propose a series of ethical guideposts developed by engaging RbT practitioners in reflecting on their practice. Like signs on a highway, ethical guideposts do not mandate a destination but rather flag that an approaching decision needs consideration. These guideposts seek to encourage greater attention to ethical aspects of RbT projects and to support ethical decision-making.